Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(P=1+1/2(2.3/2)+1/3(3.4/2)+...+1/16(16.17/2) P=1+3/2+4/2+...+17/2 P=(2+3+4+...+17)1/2 \)
2.(x-1)-3.(2x+2)-4.(2x+3)=16
=>2x-2-6x-6-8x-12=16
=>2x-6x-8x-(2+6+12)=16
=>x.(2-6-8)=16+20=36
=>x.(-12)=36
=>x=-3
Vậy x=-3
\(2\left(x-1\right)-3\left(2x+2\right)-4\left(2x+3\right)=16\)
\(\Leftrightarrow2x-2-6x-6-8x-12=16\)
\(\Leftrightarrow\left(2x-6x-8x\right)+\left(-2-6-12\right)=16\)
\(\Leftrightarrow-12x-20=16\)
\(\Leftrightarrow-12x=36\)
\(\Leftrightarrow x=\frac{-36}{12}-3\)
\(S=2^{2010}-\left(2^{2009}+2^{2008}+...+2+1\right)\)
Đặt \(A=2^{2009}+2^{2008}+...+2+1\)
\(\Rightarrow2A=2^{2010}+2^{2009}+...+2^2+2\)
\(\Rightarrow2A-2^{2010}+1=2^{2009}+2^{2008}+...+2+1\)
\(\Rightarrow2A-2^{2010}+1=A\)
\(\Rightarrow A=2^{2010}-1\)
\(\Rightarrow S=2^{2010}-A=2^{2010}-\left(2^{2010}-1\right)=1\)
b/ Ta có công thức \(1+2+3+...+n=\dfrac{n\left(n+1\right)}{2}\)
Do đó:
\(P=1+\dfrac{1+2}{2}+\dfrac{1+2+3}{3}+...+\dfrac{1+2+3+...+16}{16}\)
\(P=1+\dfrac{2.3}{2.2}+\dfrac{3.4}{2.3}+\dfrac{4.5}{2.4}+...+\dfrac{16.17}{2.16}\)
\(P=1+\dfrac{1}{2}\left(3+4+5+...+17\right)\)
\(P=1+\dfrac{1}{2}.\dfrac{\left(17-3+1\right)\left(3+17\right)}{2}=76\)